MENCEGAH PERGAULAN BEBAS BAGI REMAJA - Sriwani Hutabarat; Sebastian Purba; Yosef A. Situmorang; Damayanti Nababan (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
The problem of promiscuity among teenagers poses a major challenge to their growth and overall well-being. The aim of this scientific study is to explain the importance of preventing promiscuity and offer practical strategies to effectively curb this behavior.By reviewing related literature and secondary data, this research uses descriptive-analytic techniques. The research results show that teenage promiscuity can have negative impacts, such as the potential for teenage pregnancy, transmission of sexually transmitted diseases, drug abuse, and the development of mental health disorders.Comprehensive and appropriate sexual education plays an important role in preventing promiscuity. By providing teens with accurate information and improving decision-making skills regarding relationships, sexual activity, and contraception, effective sexual education can effectively encourage healthy choices.